Post-covid Syndrome Prevalence: A Systematic Review And Meta-analysis - Ruhana Sk Abd Razak; Aniza Ismail; Aznida Firzah Abdul Aziz; Leny Suzana Suddin; Amirah Azzeri; Nur Insyirah Sha’ari (BioMed Central Ltd, 2024)
Indexed by WOS/Scopus/ERA